The effect of the flipped classroom approach and self-efficacy on a guided inquiry on students' creative thinking skills - Dian Indah Lestari; Muhammad Haris Effendi-Hasibuan; Damris Muhammad (Jurnal Pendidikan Kimia (JPKim), 2020)
This study aims to look at the effect of the flipped classroom approach on the guided inquiry model and student's self-efficacy on creative thinking skills on the reaction rate material. The study was conducted in class XI MIA SMA N 3 Jambi City with a 2 x 2 factorial design and the sample consisted of 2 classes chosen randomly. Data collection using test techniques, namely essay tests, includes indicators of creative thinking and non-tests, namely self-efficacy questionnaire data and field notes during the study. Analysis of the data used is 2-way ANOVA. The results showed that guided inquiry learning with the flipped classroom approach and high self-efficacy categories had high creative thinking abilities, but there is no interaction between learning models with self-efficacy towards creative thinking abilities on the reaction rate material because learning models and self-efficacy affect the results of students' creative thinking abilities independently. Based on the results of the study it can be concluded: (1) There is an influence of the flipped classroom approach on the guided inquiry model of students 'creative thinking abilities on the reaction rate material (2) There is an effect of students' self-efficacy on the ability to think creatively on the material reaction rate (3) There was no interaction between the learning model and students' self-efficacy.Keywords: Creative thinking skills, Flipped classroom, Guided inquiry, Reaction rate, Self-efficacy